The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1093/pasj/psv122
|View full text |Cite
|
Sign up to set email alerts
|

Confrontation of top-hat spherical collapse against dark halos from cosmological N-body simulations

Abstract: The top-hat spherical collapse model (TSC) is one of the most fundamental analytical frameworks to describe the non-linear growth of cosmic structure. TSC has motivated, and been widely applied in, various researches even in the current era of precision cosmology. While numerous studies exist to examine its validity against numerical simulations in a statistical fashion, there are few analyses to compare the TSC dynamics in an individual object-wise basis, which is what we attempt in the present paper. We extr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…The NFW halo is assumed to be radially symmetric and requires truncation at a finite radius in order to prevent the integrated mass diverging as r → ∞. The truncation is typically set by the virial radius, which is itself determined approximately via the spherical top-hat collapse model describing the evolution of a uniform spherical overdensity in a smooth expanding background (White 2001;Suto et al 2016;Herrera, Waga, & Jorás 2017). Gravitational collapse of the overdensity halts when virial equilibrium is reached.…”
Section: Semi-analytic Halosmentioning
confidence: 99%
“…The NFW halo is assumed to be radially symmetric and requires truncation at a finite radius in order to prevent the integrated mass diverging as r → ∞. The truncation is typically set by the virial radius, which is itself determined approximately via the spherical top-hat collapse model describing the evolution of a uniform spherical overdensity in a smooth expanding background (White 2001;Suto et al 2016;Herrera, Waga, & Jorás 2017). Gravitational collapse of the overdensity halts when virial equilibrium is reached.…”
Section: Semi-analytic Halosmentioning
confidence: 99%
“…Actually, the difference between the model prediction and the simulation results is not peculiar to EC. In Suto et al (2016), we compare the evolution of the spherical radius of individual simulated halos with the prediction of the spherical collapse model. We then showed that the spherical collapse model fairly well reproduce the evolution of the simulation results up to the turn-around epoch.…”
Section: Comparison Of Evolution Of Individual Halos With Ec Predictionmentioning
confidence: 99%
“…This suggests that the self-similar solution may capture the overall trends in the dynamics of accreting material on to CDM halos in simulations, and possibly those in the real universe if the CDM scenario is true, although it is very hard to imagine that spherically symmetric and isolated halo is realized in reality. In fact, even when starting from a nearly spherically symmetric initial condition, non-sphericity is rapidly developed due to the so-called radial-orbit instability (e.g., Binney & Tremaine 2008), and a deviation from the top-hat spherical collapse model is significant (Suto et al 2016a). The resultant halo exhibits an elongated triaxial shape (e.g., Jing & Suto 2002;Suto et al 2016b), rather different from the prediction of the self-similar solution (e.g., MacMillan et al 2006).…”
Section: Introductionmentioning
confidence: 99%